Síntese, caracterização espectroscópica e estudo do comportamento térmico dos nalidixatos de lantanídeos trivalentes - Návia, Marcos Vinícius Dobies [UNESP] (Universidade Estadual Paulista (Unesp), 2017)
Due the metallic ions' importance into the biological system, principally through interaction with drug administered for therapeutic purposes, the metallic complexes have become a subject of great interest research. In this work the light trivalent lanthanide nalidixates were synthesized in aqueous solution. The thermoanalytical data allowed to establish the stoichiometry for the compounds, where the general formula is Ln(nal)3.nH2O (where Ln is the representation of the lanthanide (III) ions, nal the nalidixate ligand and n is the number of water molecules of hydration). The TG-DTA and TG / DTG curves of the compounds showed the thermal decomposition of the compounds occurs in consecutive steps a/o overlapping. The X-ray diffractograms by the powder method revealed that the compounds exhibit low crystallinity, probably due to the quickly precipitation of the lanthanide (III) nalidixates. The absorption spectroscopy data in the infrared region suggest that the lanthanide (III) nalidixates interact by coordinating in a bidentate-chelating manner

Dada a importância dos íons metálicos em sistemas biológicos, principalmente pela interação com drogas administradas para fins terapêuticos, os complexos metálicos tornaram-se um assunto de grande interesse de pesquisa. No presente trabalho foram sintetizados em solução aquosa os nalidixatos de lantanídeos trivalentes leves. Os dados termoanalíticos permitiram estabelecer a estequiometria para os compostos, obtendo a fórmula geral Ln(nal)3.nH2O (sendo Ln a representação dos íons lantanídeos (III), nal o ligante nalidixato e n é o número de moléculas de água de hidratação do composto), de tal forma que n = 5 para o Nd e La e n = 6 para o Ce, Pr e Sm. As curvas TG-DTA e TG/DTG dos compostos mostraram que a decomposição térmica dos compostos ocorre em etapas consecutivas e/ou sobrepostas. Os difratogramas de raios X, realizados pelo método de pó revelaram que os compostos apresentam baixa cristalinidade, o que se dá, provavelmente, pela rápida precipitação dos nalidixatos de lantanídeos (III). Os dados da espectroscopia de absorção na região do infravermelho sugerem que os nalidixatos de lantanídeos (III) se interagem coordenando-se de forma bidentada-quelante
Synthesis, spectroscopic characterization and study of the thermal behavior of trivalent lanthanide nalidixates
Keywords: Ions metalicos; Metais de terras raras; Materiais compostos; Análise espectral; Rare earth metals